Theoretical Principle of Narratology and Translating Narrative Texts - Horri, Abolfazl (Iranian Journal of Translation Studies, 2007)
This paper examines the relationship between narratology and translated narrative texts. Firstly, it reviews the literature. It then examines different narrative communication models in translated narrative texts. The narrative model has but a direct relationship with the narrator, a voice that narrates the text. With translated narrative text, however, comes to the scene another voice, which is the translator's and is as important as the narrator's. This voice belongs to the translator, who will be the voice of the narrator of the translation. Therefore, it is necessary to take into account the translator as one of the main components in translated narrative model.